MoS 2 Modification to Enhance the Removal of Various Chlorinated Hydrocarbons by Zerovalent Iron - Chen, JiaXin; Feng, Yiran; Liu, Yabo; Fan, Peng; Ao, Zhimin; Qin, Hejie; Guan, Xiaohong (Environmental science & technology, 2025)
Various methods have been developed to enhance the performance of zerovalent iron (ZVI) for chlorinated hydrocarbon (CHC) removal, but their applicability across diverse CHCs remains limited. Here, we present a MoS modification strategy to address these challenges. MoS -modified ZVI (MoS -ZVI) exhibited dechlorination rate constants that are 1.25 to 54 times those obtained with ZVI, for eight representative CHCs, with significantly fewer incompletely dechlorinated products. The electron efficiency values increased to 2.7-26.5 times, with the synchronously inhibited H evolution possibly resulting from the increased hydrophobicity caused by MoS modification. While H contributes to the reduction of certain CHCs, the enhancement by MoS is mainly attributed to improved electron transfer at the surface. Characterization results revealed partial integration of MoS with ZVI and the presence of sulfur vacancies on MoS surfaces in MoS -ZVI. Electrochemical experiments with separated ZVI and MoS in different compartments identified sulfur vacancies as the reactive sites. In situ Fourier transform infrared spectroscopy and density functional theory results demonstrated that CHCs adsorb at Mo sites exposed by sulfur vacancies, and this process is facilitated by the integrated effects of underlying ZVI. The dechlorination of CHCs subsequently occurs with the electrons transferred from ZVI to the surface-bonded CHC through the MoS layer. This study provides a broadly applicable modification strategy for achieving rapid, full, and selective dechlorination of a wide range of CHCs.